A Case of an Increase in Prothrombin Time-International Normalized Ratio by Interaction Between Warfarin and Baloxavir Marboxil in a Patient on Implantable Ventricular Assist Device - Keiko Kurosawa; Shinya Takasaki; Hisaki Suzuki; Yuji Sato; Masatoshi Akiyama; Miki Akiba; Yoshikatsu Saiki; Nariyasu Mano (Journal of Pharmacy & Pharmaceutical Sciences, 2021)
Background: Baloxavir marboxil (BM) is a novel drug with a cap-dependent endonuclease inhibitory action for influenza A or B; it is highly safe and requires just a single oral dose. Patients with severe heart failure use implantable ventricular assist device (iVAD) until transplantation, but they have an increased risk of thrombosis development. Their warfarin is administered based on point-of-care testing (POCT) with a strict control of prothrombin time-international normalized ratio (PT-INR). Case report: Here, we report a case of a patient with iVAD whose PT-INR was significantly increased from the target range after BM administration. The patient was a 45-year-old man and transplanted with iVAD; warfarin treatment was started when his PT-INR target range was 3.0–3.5. At home, he frequently self-measured PT-INR by POCT and precisely controlled the warfarin dose. He had a fever, was diagnosed with influenza A and was administered BM 40 mg. Thereafter, his PT-INR continued to increase, reaching 4.8 on day 12 of BM administration, exceeding his target range; warfarin was skipped for 1 day. In this case, based on the history of BM administration and clinical course, the increase in PT-INR could be due to BM. Considering the interaction between warfarin and BM, we suspected a possibility of competition for protein-binding sites. Increased PT-INR in the patient was detected early by POCT and thus severe bleeding was avoided. Conclusion: Strict monitoring of PT-INR when using BM in patients taking warfarin is of clinical importance.